Xizmät tori (2021)
Ein Jobportal in uigurischer Sprache im Uigurischen Autonomiegebiet Xinjiang der Volksrepublik China. Auf dieser Online-Jobbörse werden unterschiedliche Stellenangebote und Stellengesuche in der freien Wirtschaft in Xinjiang publiziert. - A job portal in Uyghur language in the Xinjiang Uyghur Autonomous Region of the People's Republic of China. On this online job portal, different job offers and job requests in the free economy in Xinjiang are published.